Effect of average beam power on microstructure and mechanical properties of Nd: YAG laser welding of 304L and st37 steel. (10th June 2019) - Kumar, Pramod; Sinha, Amar Nath
Abstract : Purpose: The present research work aims to study the effect of average beam power (laser process parameters) on the overlapping factor, depth of penetration (DOP), weld bead width, fusion zone and heat affected zone (HAZ) in laser welding of 304L and st37 steel. Back side and top surface morphology of the welded joints have also been studied for varying average beam power. Design/methodology/approach: Laser welding of austenitic stainless steel (304L) and carbon steel (st37) was carried out using Nd:YAG laser integrated with ABB IRB 1410 robot in pulse mode. The selection of laser process parameters was based on the specification of available laser welding machine. Dissimilar laser welding of 304L and st37 carbon steel for full depth of penetration have been performed, with varying average beam power (225-510W) and constant welding speed (5mm/s) and pulse width (5ms). Findings: Recrystallized coarse grains were observed adjacent to the fusion zone and nucleated grains were seen away from the fusion zone towards carbon steel. Overlapping factor and HAZ width st37 side increases with increase in average beam power whereas top weld bead width increases first, attains maximum value and then subsequently decreases. Bottom weld bead width increases with increase in average beam power. The mechanical properties namely microhardness and tensile strength of the welded joints have been investigated with varying average beam power. Originality/value: In the recent development of the automobile, power generation and petrochemical industries the application of dissimilar laser welding of austenitic stainless steel (304L) and carbon steel (st37) are gaining importance. Very limited work have been reported in pulsed Nd:YAG dissimilar laser welding of austenitic stainless steel (304L) and carbon steel (st37) for investigating the effect of laser process parameters on weld bead geometry, microstructural characterization and mechanical properties of the welded joint.